Restorations of Endodontically Treated Teeth - Hale Cimilli; Şevval Sena Ak (Selcuk Dental Journal)
Endodontically treated teeth are fragile compared to vital teeth. The reason for the decrease in fracture resistance and hardness is related to the deterioration of the structural integrity as a result of caries, trauma and cavity preparation. Restorations in endodontically treated teeth are applied considering the remaining tooth structure and functional status. For many years, post core systems that require additional preparation in the root canal, as well as the loss of most of the coronal tooth structures, are used for the final restoration of endodontically treated teeth. Endocrowns are monoblock restorations that attach to the pulp chamber and its walls, providing macro-mechanical and cementation with micro-mechanics, thus requiring no additional preparation. The first study written on ceramic endocrown was published in 1995. In this study, it is defined as a ceramic monoblock production technique for the restoration of endodontically treated teeth. This procedure was later named "endocrown" in 1999.